(3efGbH fGUQ GdOjf heZGRjgs - (3eMeO GdjOGdj Hf GdeNJGQ Hf eMeO SYjO GdOjeGfj,J (B1164 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3fGbU hChd GdehLhO efg (B: (3MOKfi QLd ef ChdG CHjHQ ef EOGHge GSeg GdeNJGQ Hf YeQ hcGf ef JGLcGfJ hcGf eYge ai eMGQHI GdYQhSSf bGd QcHJ PGJ jhe ai CjGe Jdc s
(3BNQgG (B:s
(3Efi BNP cJGHi HTeGd abGd Hg EfeG bdJ Efi QCjJ aWGHJ faSg hCfUQa adeG eVi bGd dHYV LdSGFg CfgG GdTjeI GdJi HYVOg Je hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG BKGQ QWhHI CJJ Ydi HYV LhGfH ChQGbgG aGVGYJ HYV cdeGJgGs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdJGQjNs